2022
DOI: 10.26877/jp2f.v13i2.12794
|View full text |Cite
|
Sign up to set email alerts
|

Profil Kemampuan Berpikir Komputasional (Computational Thinking) Siswa SMP Negeri Se-Kota Semarang Tahun 2022

Abstract: This study aims to determine the profile of the mastery of computational thinking skills of State Junior High School students throughout the city of Semarang with the benefit of being a benchmark for innovation or development of learning models oriented to mastering the computational thinking skills of State Junior High School students in the city of Semarang. This research was conducted in 15 public junior high schools in the city of Semarang on March 25, 2022 - April 30, 2022. The sample in the study amounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…critical thinking, communication, creative thinking, and collaboration skills. Computational thinking skills are included in the 5 Cs, previously only 4C because they are needed to improve students' skills in solving complex problems (Azmi & Ummah, 2021;Nuvitalia et al, 2022;Sa'diyyah, 2021). The development of 21st-Century education requires creative, critical, and computational thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…critical thinking, communication, creative thinking, and collaboration skills. Computational thinking skills are included in the 5 Cs, previously only 4C because they are needed to improve students' skills in solving complex problems (Azmi & Ummah, 2021;Nuvitalia et al, 2022;Sa'diyyah, 2021). The development of 21st-Century education requires creative, critical, and computational thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers say that PjBL has a syntax that can support contextual learning and 21st century skills (Afriana et al, 2016;Ardiansyah et al, 2020;Avery & Reeve, 2013;Reeve, 2011). Furthermore, STEM has also been heavily integrated with PjBL through systematic project completion of contextual problems that occur daily (Lou et al, 2017;Ngoh, 2013;Tseng et al, 2013). The completion of the project is carried out according to student worksheets designed by the teacher and specifically aimed at improving students' 21st century skills.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Nuvitalia et al (2022) in ninth-grade students showed that the level of students' mathematical critical thinking ability was in the medium category with a presentation of abstraction of 56.19%, generalization of 58.73%, pattern recognition of 46.03%, decomposition of 53.24%, and algorithms of 51.74%. In addition, research conducted by Paf and Dincer (2021) found that students' computational thinking skills had a favourable and concrete relationship to creative problem-solving abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Students demonstrated high-level problem-solving abilities by compiling steps to tackle the same difficulties. According toNuvitalia et al (2022), thinking algorithms write automated solutions through algorithmic thinking or sequential steps. The last percentage achieved by the pattern recognition indicator reached 65%.…”
mentioning
confidence: 99%